Preparation method for depositing TiC coating on surface of crystalline flake graphite by using molten salt method

The deposition of TiC coating on the surface of scale graphite through molten salt method and ball milling process solves the problems of large inertia and poor wetting on the surface of scale graphite, and achieves an efficient and dense titanium carbide coating, which improves the application performance and stability of scale graphite.

CN119240687APending Publication Date: 2025-01-03SHENYANG UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411142252.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The surface of scale graphite is very inert, difficult to bond well with metal substrates, and poor wetting properties, which limits its application in composite materials. Existing deposition methods such as electroless plating or electroplating are difficult to ensure the integrity and uniformity of the interface coating, and The equipment is complex or the energy consumption is high.

Method used

The TiC coating was deposited on the surface of scale graphite by molten salt. The titanium powder and molten salt were fully mixed through ball milling and vertical powder mixing technology to reduce the surface reaction temperature of titanium atoms and scale graphite. The vacuum tube furnace was used to form titanium carbide at high temperature. Coating, combined with pickling method, remove residues, and improve the density and bonding power of the coating.

Benefits of technology

The dense continuity and high binding force of the titanium carbide coating on the surface of the scale graphite is realized, the deposition efficiency and stability of the coating are improved, the coating is avoided, the coating is dissipated and diffused, the equipment and processes are simplified, and the anti-oxidation of the titanium graphite is enhanced. Performance and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005001187690000011
    Figure HDA0005001187690000011
  • Figure HDA0005001187690000021
    Figure HDA0005001187690000021
Patent Text Reader

Abstract

The invention belongs to the technical field of metal matrix composite materials, and relates to a preparation method for depositing a TiC coating on the surface of crystalline flake graphite by using a molten salt method, which comprises the following steps: carrying out surface oil removal treatment on the crystalline flake graphite to remove organic matters on the surface of the crystalline flake graphite: carrying out ball-milling mixing on molten salt and titanium powder to obtain uniformly mixed powder A; mixing the mixed powder A with crystalline flake graphite to obtain uniformly mixed powder B; the mixed powder B is placed in a vacuum tube furnace, the surface of crystalline flake graphite is plated with a TiC coating, and TiC-crystalline flake graphite mixed powder is prepared; and the prepared TiC-crystalline flake graphite mixed powder is subjected to chlorine salt removal and redundant titanium powder removal treatment, pure TiC-crystalline flake graphite is obtained, the pure TiC-crystalline flake graphite is placed in a vacuum drying oven to be dried, and the pure TiC-crystalline flake graphite is taken out of the vacuum drying oven and stored in a sealed mode. According to the invention, the problems of high surface inertia and poor wettability between the flake graphite and a metal matrix are solved, so that the oxidation resistance of the flake is improved, and the surface performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal-based composite materials and relates to a preparation method for depositing a TiC coating on the surface of flake graphite by using a molten salt method. Background Art

[0002] Flake graphite is a carbon material with a high degree of graphitization and crystallinity, which gives it extremely high planar thermal conductivity, low thermal expansion coefficient and good electrical conductivity, so that its application in metal-based composites can bring a series of advantages such as high thermal conductivity, good mechanical properties, excellent electrical conductivity, low thermal expansion coefficient, light weight and strong corrosion resistance. These characteristics make flake graphite / metal composites have broad application prospects in high-tech fields. However, although flake graphite has many advantages, its graphite structure leads to large surface inertia and lacks active functional groups, so it has poor adhesion to the matrix and a series of interface problems, which limit its application to a certain extent. In addition, it is difficult for flake graphite to infiltrate metal matrices such as aluminum, copper or magnesium. Therefore, it is particularly important to modify the surface of flake graphite. The methods used to improve the relationship between flake graphite and metal matrix can be divided into two categories. One is to add alloy elements to the metal matrix, and generate an interface coating on the surface of flake graphite by element enrichment and original self-generation methods. However, this method is difficult to ensure the integrity and uniformity of the interface coating. At the same time, the addition of alloying elements will also affect the composition and performance of the base metal itself. Another method is to pre-deposit a uniform and continuous coating on the surface of flake graphite by various chemical or physical methods. This coating is not only easy to control, but also will not pollute the metal substrate, so it has more development advantages.

[0003] At present, common coatings deposited on the surface of flake graphite include Cu, Ni, Zn and Sn coatings, which can be prepared by chemical plating or electroplating. The advantages are high coating deposition efficiency and simple equipment. However, due to the principle of chemical deposition and the characteristics of the flake graphite surface, the deposited coating is simply physically bonded to the flake graphite, and its interface bonding ability is weak, which is easy to fall off and diffuse during the preparation of composite materials. Compared with these metal coatings, titanium carbide coating has excellent wear resistance, hardness and high temperature stability. It can enhance the mechanical properties and thermal stability of flake graphite, and also improve the wettability between flake graphite and metal liquid. The methods commonly used to prepare titanium carbide coatings on the surface of flake graphite include self-propagating high temperature synthesis, solution impregnation and chemical vapor deposition. Among them, the self-propagating high temperature synthesis method usually uses flake graphite and titanium powder as raw materials, and uses the heat generated by the highly exothermic reaction between the reactants to maintain the continuous reaction, thereby preparing a titanium carbide coating. The titanium carbide coating generated by this method has a relatively high purity, but the reaction process is rapid and violent, the reaction temperature and reaction rate are difficult to accurately control, and the coating prepared by carbon may have pores and defects. The basic principle of the solution impregnation method is to immerse the flake graphite to be coated in a solution containing a titanium source and a carbon source, and form a titanium carbide coating on the surface of the substrate through appropriate chemical reactions or heat treatments. This method has the advantages of simple process and low equipment requirements, but this method also has problems such as difficult control of coating uniformity, weak bonding between the coating and the substrate, large influence of heat treatment on the coating performance, and easy solution residue. The chemical vapor deposition method is to form a titanium carbide coating by chemically reacting the gaseous titanium source and carbon source on the surface of the flake graphite at high temperature. The titanium carbide coating prepared by this method is relatively dense and has a high bonding strength with the substrate, but the process equipment is complex and expensive, and has the disadvantages of high energy consumption and harsh reaction conditions, making it impossible to use it on a large scale in industrial production. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a preparation method for depositing a TiC coating on the surface of flake graphite using a molten salt method, thereby overcoming the problems of high surface inertness of flake graphite and poor wettability with a metal matrix, so as to improve the anti-oxidation performance of the flakes, improve their surface properties, enhance mechanical properties and promote application expansion.

[0005] The present invention is achieved in this way.

[0006] A preparation method for depositing a TiC coating on the surface of flake graphite using a molten salt method comprises the following steps:

[0007] S1 performs surface degreasing treatment on the flake graphite to remove organic matter on the surface of the flake graphite, and then cleans and dries the degreasing surface of the flake graphite:

[0008] S2: ball-milling the molten salt and titanium powder to obtain a uniformly mixed mixed powder A; mixing the mixed mixed powder A with flake graphite to obtain a uniformly mixed mixed powder B;

[0009] S3: placing the mixed powder B in a vacuum tube furnace, coating the surface of the flake graphite with a TiC coating, and preparing a TiC-flake graphite mixed powder;

[0010] S4 removes chloride salt and excess titanium powder from the prepared TiC-flake graphite mixed powder to obtain pure TiC-flake graphite, which is then placed in a vacuum drying oven for drying, and finally taken out from the vacuum drying oven and sealed for storage.

[0011] Further: the degreasing liquid in S1 is configured as follows: deionized water is used as solvent, and the chemical liquid is prepared according to the proportions of 8g / L-20g / L sodium hydroxide, 10g / L-20g / L sodium carbonate, and 10g / L-20g / L sodium phosphate;

[0012] The addition amount of flake graphite in degreasing is 0.5g / L-3g / L, the temperature is maintained at 60℃-80℃, the processing time is 8min-20min, and electromagnetic stirring is applied at 25r / min-75r / min during the whole degreasing process;

[0013] The degreased flake graphite surface is cleaned in the following steps: first, use deionized water at 45°C-65°C as a cleaning agent for 5min-10min, and then use anhydrous ethanol as a cleaning agent for 3min-5min. During the entire cleaning process, electromagnetic stirring at 50r / min-100r / min is applied.

[0014] Furthermore: In S2, the molten salt includes KCl and NaCl, and the molar ratio of KCl:NaCl is 1:1, the mass ratio of the molten salt to the titanium powder is 5:1, and the mass ratio of the mixed powder A to the flake graphite is 15:1.

[0015] Further: In S2, when preparing mixed powder A, the method used is ball milling, the ball milling speed is 150r / min-250r / min, and the ball milling time is 0.5h-3h; when preparing mixed powder B, the vertical mixing method is adopted, the mixing speed is 40r / min-80r / min, and the mixing time is 0.5h-2h.

[0016] Further: In S3, the mixed powder B is first placed in a square corundum crucible of 5 cm*3 cm*15 cm and flattened, the corundum crucible is equipped with a crucible cover, and then the square corundum crucible is placed in a vacuum tube furnace.

[0017] Further: the vacuum tube furnace heating rate is 2°C / min-8°C / min, the molten salt reaction temperature is 700°C-1100°C, the reaction time is 1h-3h, the protective gas is argon, and the gas flow rate is 3ml / min-15mL / min.

[0018] Further: In S4, the residual chloride salt in the TiC-flake graphite mixed powder is removed by boiling method, the reagent is deionized water, the dechlorination temperature is 100° C., and the dechlorination time is 10 min-30 min.

[0019] Further: the titanium powder remaining in the TiC-flake graphite mixed powder after chlorination is removed by pickling, the reagent is 35%-55% sulfuric acid solution, and the amount of TiC-flake graphite mixed powder added to the sulfuric acid solution is 0.3g / L-3g / L.

[0020] Furthermore: the pickling temperature is 60°C-80°C, the pickling time is 5min-15min, and electromagnetic stirring is applied at 30r / min-50r / min during the entire cleaning process.

[0021] Further: after the pickling is completed, rinse with deionized water and place in a drying oven for drying, the drying temperature is 80°C-150°C, and the drying time is 3h-8h.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] Compared with the flake graphite without degreasing, the strong alkali degreasing process added in the present invention can reduce the pollutants of the coating components caused by organic matter deposited on the surface of the flake graphite during transportation and storage, and also increase the contact efficiency between the flake graphite and the titanium powder.

[0024] The present invention adopts a secondary powder mixing process, which has the advantage that when mixing the powder through the ball milling process, in addition to fully mixing the titanium powder and the molten salt powder, the particle size of the mixed powder can also be regulated to ensure that it can be better mixed with the flake graphite. The secondary vertical powder mixing method adopted can avoid uneven powder mixing caused by density difference, and this method can reduce damage to the flake graphite during the powder mixing process.

[0025] The molten salt process used in the present invention uses molten salt as a reaction pool to accelerate the enrichment of titanium ions to the surface of flake graphite, and also reduces the reaction temperature of titanium atoms and carbon atoms on the surface layer of flake graphite, thereby reducing energy consumption and improving coating deposition efficiency. When the titanium carbide coating is deposited on the surface of flake graphite using the molten salt method, due to the effect of the molten salt pool, the chemical reaction temperature of titanium powder and the surface of flake graphite can be reduced, thereby reducing energy consumption and improving deposition rate. Under the condition of vacuum state and reduced reaction temperature, the oxidation and volatilization of the reactants at high temperature can also be effectively prevented, and the introduction of impurities can be reduced. At the same time, the high temperature reaction conditions in the molten salt method help to form a stronger chemical bond or mechanical bite between titanium carbide and the surface of flake graphite, thereby improving the bonding force between the coating and flake graphite, and this strong bonding force makes the coating difficult to fall off or peel off during the preparation of metal-based composite materials. Therefore, the titanium carbide coating prepared on the surface of flake graphite using this process is not only dense and continuous and has strong bonding force, but also simple in equipment and process, which can greatly improve the deposition efficiency of the titanium carbide coating on the surface of flake graphite. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The surface morphology of flake graphite before titanium carbide coating under scanning electron microscope (a) and energy spectrum results (b);

[0027] Figure 2 The surface morphology image (a) and energy spectrum result (b) of flake graphite coated with titanium carbide coating under a scanning electron microscope provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] Example 1

[0030] A preparation method for depositing a TiC coating on the surface of flake graphite using a molten salt method comprises the following steps:

[0031] S1 Before depositing TiC coating on the surface of flake graphite, the flake graphite was first degreased to remove organic matter on the surface of the flake graphite. Deionized water was used as the solvent, and the chemical solution was prepared according to 8g / L sodium hydroxide, 10g / L sodium carbonate, and 10g / L sodium phosphate. The amount of flake graphite added during the degreasing process was 0.5g / L, the temperature was maintained at 60°C, the treatment time was 8min, and electromagnetic stirring was applied at 25r / min during the entire degreasing process.

[0032] The degreased flake graphite surface was cleaned in the following steps: first, deionized water at 45° C. was used as a cleaning agent for 5 min, and then anhydrous ethanol was used as a cleaning agent for 3 min. During the entire cleaning process, electromagnetic stirring was applied at 50 r / min.

[0033] S2: ball-milling the molten salt and titanium powder to obtain a uniformly mixed mixed powder A; mixing the mixed mixed powder A with flake graphite to obtain a uniformly mixed mixed powder B;

[0034] Molten salt configuration: Molten salt type and molar ratio: KCl: NaCl is 1:1, the mass ratio of molten salt to titanium powder is 5:1, and the molten salt and titanium powder are mixed into mixed powder A by ball milling, the ball milling speed is 150r / min, and the ball milling time is 3h. The mixed powder A is mixed with flake graphite by vertical mixing method to form mixed powder B, the mass ratio of mixed powder A to flake graphite is 15:1, and when preparing mixed powder B, the mixing speed is 40r / min, and the mixing time is 2h.

[0035] S3 coating preparation, the mixed powder B is placed in a vacuum tube furnace, and a TiC coating is plated on the surface of the flake graphite to prepare a TiC-flake graphite mixed powder: first, the mixed powder B is placed in a 5cm*3cm*15cm square corundum crucible and flattened, and the corundum crucible is equipped with a crucible cover, and then the square corundum crucible is placed in a vacuum tube furnace for heating. The vacuum tube furnace heating rate is 2℃ / min, the molten salt reaction temperature is 700℃, the reaction time is 1h, the protective gas is argon, and the gas flow rate is 3ml / min. After the reaction is completed, the TiC-flake graphite mixed powder is obtained.

[0036] S4 removes chloride salt and excess titanium powder from the prepared TiC-flake graphite mixed powder to obtain pure TiC-flake graphite, which is then placed in a vacuum drying oven for drying, and finally taken out from the vacuum drying oven and sealed for storage.

[0037] The method comprises: using a boiling method to remove the residual chloride salt in the TiC-flake graphite mixed powder, the reagent is deionized water, the dechlorination temperature is 100°C, and the dechlorination time is 10 minutes. Then, the titanium powder remaining in the TiC-flake graphite mixed powder after dechlorination is removed by an acid pickling method, the reagent is a 35% sulfuric acid solution, the amount of TiC-flake graphite mixed powder added to the sulfuric acid solution is 0.3g / L, the pickling temperature is 80°C, the pickling time is 5 minutes, and an electromagnetic stirring of 30r / min is applied during the entire cleaning process. After the pickling is completed, rinse it with deionized water and place it in a drying oven for drying, the drying temperature is 80°C, the drying time is 8 hours, and finally take it out and seal it for storage. The prepared titanium carbide coating is uniform and consistent, without leakage plating, and the titanium carbide coating is well combined with the fiber.

[0038] Embodiment 2:

[0039] S1 performs surface degreasing treatment on the flake graphite to remove organic matter on the surface of the flake graphite, and then cleans and dries the degreasing surface of the flake graphite, including:

[0040] Before depositing the TiC coating on the surface of the flake graphite, the flake graphite is first subjected to surface degreasing treatment to remove organic matter on the surface of the flake graphite. Deionized water is used as the solvent, and the chemical liquid is mixed according to 20g / L of sodium hydroxide, 20g / L of sodium carbonate, and 20g / L of sodium phosphate. The amount of flake graphite added during the degreasing process is 3g / L, the temperature is maintained at 80°C, the treatment time is 20min, and 75r / min of electromagnetic stirring is applied during the entire degreasing process. Then the surface of the degreased flake graphite is cleaned. The cleaning steps are: first use 65°C deionized water as a cleaning agent to clean for 10min, and then use anhydrous ethanol as a cleaning agent to clean for 5min. 100r / min of electromagnetic stirring is applied during the entire cleaning process.

[0041] S2: ball-milling the molten salt and titanium powder to obtain a uniformly mixed mixed powder A; mixing the mixed mixed powder A with flake graphite to obtain a uniformly mixed mixed powder B; wherein,

[0042] Molten salt configuration: Molten salt type and molar ratio: KCl: NaCl is 1:1, the mass ratio of molten salt to titanium powder is 5:1, and the molten salt and titanium powder are mixed into mixed powder A by ball milling, the ball milling speed is 250r / min, and the ball milling time is 0.5h. The mixed powder A is mixed with flake graphite by vertical mixing method to form mixed powder B, and the mass ratio of mixed powder A to flake graphite is 15:1. When preparing mixed powder B, the mixing speed is 80r / min, and the mixing time is 0.5h.

[0043] S3 coating preparation, the mixed powder B is placed in a vacuum tube furnace, and a TiC coating is plated on the surface of the flake graphite to prepare a TiC-flake graphite mixed powder: first, the mixed powder B is placed in a 5cm*3cm*15cm square corundum crucible and flattened, and the corundum crucible is equipped with a crucible cover, and then the square corundum crucible is placed in a vacuum tube furnace for heating. The vacuum tube furnace heating rate is 8℃ / min, the molten salt reaction temperature is 1100℃, the reaction time is 3h, the protective gas is argon, and the gas flow rate is 15mL / min. After the reaction is completed, the TiC-flake graphite mixed powder is obtained.

[0044] S4: Remove chloride salts and excess titanium powder from the prepared TiC-flake graphite mixed powder to obtain pure TiC-flake graphite, then place it in a vacuum drying oven for drying, and finally take it out of the vacuum drying oven and seal it for storage. The boiling method is used to remove the residual chloride salts in the TiC-flake graphite mixed powder. The reagent is deionized water, the dechlorination temperature is 100°C, and the dechlorination time is 30min. The acid pickling method is then used to remove the residual titanium powder in the TiC-flake graphite mixed powder after dechlorination. The reagent is 55% sulfuric acid solution. The amount of TiC-flake graphite mixed powder in the sulfuric acid solution is 3g / L, the pickling temperature is 60°C, the pickling time is 15min, and an electromagnetic stirring of 50r / min is applied during the entire cleaning process. After the pickling is completed, rinse it with deionized water and place it in a drying oven for drying. The drying temperature is 150°C and the drying time is 3h. Finally, take it out and seal it for storage. The prepared titanium carbide coating is uniform and has no leakage phenomenon. The titanium carbide coating is well combined with the fiber.

[0045] Embodiment 3:

[0046] S1 performs surface degreasing treatment on flake graphite to remove organic matter on the surface of flake graphite, and then cleans and dries the surface of flake graphite after degreasing. Before depositing TiC coating on the surface of flake graphite, flake graphite is first subjected to surface degreasing treatment to remove organic matter on the surface of flake graphite, using deionized water as solvent, and mixing chemical liquids according to 15g / L sodium hydroxide, 15g / L sodium carbonate, and 15g / L sodium phosphate. The amount of flake graphite added during the degreasing process is 1g / L, the temperature is maintained at 70°C, the treatment time is 15min, and electromagnetic stirring is applied at 50r / min during the entire degreasing process. Then, the surface of flake graphite after degreasing is cleaned, and the cleaning steps are: first, use 50°C deionized water as a cleaning agent to clean for 8min, and then use anhydrous ethanol as a cleaning agent to clean for 4min, and electromagnetic stirring is applied at 80r / min during the entire cleaning process.

[0047] S2: ball-milling the molten salt and titanium powder to obtain a uniformly mixed mixed powder A; mixing the mixed mixed powder A with flake graphite to obtain a uniformly mixed mixed powder B; wherein,

[0048] Molten salt configuration: Molten salt type and molar ratio: KCl: NaCl is 1:1, the mass ratio of molten salt to titanium powder is 5:1, and the molten salt and titanium powder are mixed into powder A by ball milling, the ball milling speed is 2000r / min, and the ball milling time is 1.5h. The mixed powder A is mixed with flake graphite to form mixed powder B by vertical mixing method, and the mass ratio of mixed powder A to flake graphite is 15:1. When preparing mixed powder B, the mixing speed is 60r / min, and the mixing time is 1h.

[0049] S3 coating preparation, the mixed powder B is placed in a vacuum tube furnace, and a TiC coating is plated on the surface of the flake graphite to prepare a TiC-flake graphite mixed powder: first, the mixed powder B is placed in a 5cm*3cm*15cm square corundum crucible and flattened, and the corundum crucible is equipped with a crucible cover, and then the square corundum crucible is placed in a vacuum tube furnace for heating. The vacuum tube furnace heating rate is 6℃ / min, the molten salt reaction temperature is 950℃, the reaction time is 2h, the protective gas is argon, and the gas flow rate is 10mL / min. After the reaction is completed, the TiC-flake graphite mixed powder is obtained.

[0050] S4: Remove the chloride salt and excess titanium powder from the prepared TiC-flake graphite mixed powder to obtain pure TiC-flake graphite, then place it in a vacuum drying oven for drying, and finally take it out of the vacuum drying oven and seal it for storage. Use boiling method to remove the residual chloride salt in the TiC-flake graphite mixed powder, the reagent is deionized water, the dechlorination temperature is 100℃, and the dechlorination time is 20min. Use pickling method to remove the residual titanium powder in the TiC-flake graphite mixed powder after dechlorination, the reagent is 45% sulfuric acid solution, the amount of TiC-flake graphite mixed powder in the sulfuric acid solution is 1g / L, the pickling temperature is 70℃, the pickling time is 10min, and the electromagnetic stirring of 40r / min is applied during the whole cleaning process. After the pickling is completed, rinse it with deionized water and place it in a drying oven for drying. The drying temperature is 100℃ and the drying time is 5h. Finally, take it out and seal it for storage. The prepared titanium carbide coating is uniform and has no leakage phenomenon. The titanium carbide coating is well combined with the fiber.

[0051] The products obtained by the present invention were subjected to comparative experiments, and the results are as follows: Figure 1 (a) is the surface morphology of flake graphite before titanium carbide coating under scanning electron microscope. It can be seen from the figure that the flake graphite is elliptical with a diameter of about 1mm-1.5mm. Before the titanium carbide coating is deposited, the surface of the flake graphite is relatively rough and has some impurities and stains. Figure 1 The EDS results in (b) show that flake graphite is composed only of carbon. Figure 2 (a) shows the surface morphology of flake graphite after titanium carbide coating under scanning electron microscope. Figure 1 By comparison, it can be seen that a layer of coating is deposited on the surface of flake graphite. The surface of flake graphite deposited with titanium carbide coating is smoother, the titanium carbide coating is continuous and uniform, no leakage or obvious unevenness of the coating is observed, and the titanium carbide coating tightly covers the surface of flake graphite, and no cracks or coating shedding are observed, which shows that the bonding performance between titanium carbide coating and flake graphite is good. Figure 2The EDS results in (b) show that the titanium carbide coating deposited on the surface of flake graphite contains only carbon and titanium, and no other impurity elements, and the atomic percentage is close to 1:1, which can be determined to be a pure TiC component. It can be concluded that this process can be used to deposit a continuous, uniform and high-purity titanium carbide coating on the surface of flake graphite.

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a TiC coating by depositing it on the surface of flake graphite using a molten salt method, characterized in that: The following steps are involved: S1 performs surface degreasing treatment on the flake graphite to remove organic matter on the surface of the flake graphite, and then cleans and dries the degreasing surface of the flake graphite: S2: ball-milling the molten salt and titanium powder to obtain a uniformly mixed mixed powder A; mixing the mixed mixed powder A with flake graphite to obtain a uniformly mixed mixed powder B; S3: placing the mixed powder B in a vacuum tube furnace, coating the surface of the flake graphite with a TiC coating, and preparing a TiC-flake graphite mixed powder; S4 removes chloride salt and excess titanium powder from the prepared TiC-flake graphite mixed powder to obtain pure TiC-flake graphite, which is then placed in a vacuum drying oven for drying, and finally taken out from the vacuum drying oven and sealed for storage.

2. The method for preparing a TiC coating by depositing a TiC coating on the surface of flake graphite using a molten salt method according to claim 1, characterized in that: The degreasing liquid in S1 is configured as follows: deionized water is used as solvent, and the chemical liquid is prepared according to the proportions of 8g / L-20g / L sodium hydroxide, 10g / L-20g / L sodium carbonate, and 10g / L-20g / L sodium phosphate; The addition amount of flake graphite in degreasing is 0.5g / L-3g / L, the temperature is maintained at 60℃-80℃, the processing time is 8min-20min, and electromagnetic stirring is applied at 25r / min-75r / min during the whole degreasing process; The degreased flake graphite surface is cleaned in the following steps: first, use deionized water at 45°C-65°C as a cleaning agent for 5min-10min, and then use anhydrous ethanol as a cleaning agent for 3min-5min. During the entire cleaning process, electromagnetic stirring at 50r / min-100r / min is applied.

3. The method for preparing a TiC coating by depositing a TiC coating on the surface of flake graphite using a molten salt method according to claim 1, characterized in that: In S2, the molten salt includes KCl and NaCl, and the molar ratio of KCl:NaCl is 1:1, the mass ratio of molten salt to titanium powder is 5:1, and the mass ratio of mixed powder A to flake graphite is 15:

1.

4. The method for preparing a TiC coating by depositing a TiC coating on the surface of flake graphite using a molten salt method according to claim 1, characterized in that: In S2, when preparing mixed powder A, the method used is ball milling, the ball milling speed is 150r / min-250r / min, and the ball milling time is 0.5h-3h; when preparing mixed powder B, the vertical mixing method is adopted, the mixing speed is 40r / min-80r / min, and the mixing time is 0.5h-2h.

5. The method for preparing a TiC coating by depositing a TiC coating on the surface of flake graphite using a molten salt method according to claim 1, characterized in that: In S3, the mixed powder B is first placed in a square corundum crucible of 5 cm*3 cm*15 cm and flattened. The corundum crucible is equipped with a crucible cover, and then the square corundum crucible is placed in a vacuum tube furnace.

6. The method for preparing a TiC coating by depositing a TiC coating on the surface of flake graphite by a molten salt method according to claim 5, characterized in that: The heating rate of the vacuum tube furnace is 2℃ / min-8℃ / min, the molten salt reaction temperature is 700℃-1100℃, the reaction time is 1h-3h, the protective gas is argon, and the gas flow rate is 3ml / min-15mL / min.

7. The method for preparing a TiC coating by depositing a TiC coating on the surface of flake graphite using a molten salt method according to claim 1, characterized in that: In S4, the boiling method is used to remove the residual chloride salt in the TiC-flake graphite mixed powder, the reagent is deionized water, the dechlorination temperature is 100° C., and the dechlorination time is 10 min-30 min.

8. The method for preparing a TiC coating by depositing a TiC coating on the surface of flake graphite using a molten salt method according to claim 1, characterized in that: The titanium powder remaining in the TiC-flake graphite mixed powder after chlorination is removed by pickling, the reagent is 35%-55% sulfuric acid solution, and the amount of the TiC-flake graphite mixed powder added to the sulfuric acid solution is 0.3g / L-3g / L.

9. The method for preparing a TiC coating by depositing a TiC coating on the surface of flake graphite using a molten salt method according to claim 8, characterized in that: The pickling temperature is 60°C-80°C, the pickling time is 5min-15min, and electromagnetic stirring is applied at 30r / min-50r / min during the entire cleaning process.

10. The method for preparing a TiC coating by depositing a TiC coating on the surface of flake graphite using a molten salt method according to claim 9, characterized in that: After pickling, rinse with deionized water and place in a drying oven for drying. The drying temperature is 80℃-150℃ and the drying time is 3h-8h.